Hubungan Karakteristik Sosiodemografi, Pengetahuan, dan Praktik Personal Hygiene dengan Kejadian Anemia pada Remaja Putri di Desa Sirnagalih - Dian Pertiwi; Apriningsih; Widayani Wahyuningtyas; Feda Anisah Makkiyah (Jurnal Kesehatan Komunitas, 2022)
Anemia is a serious global public health problem and affects the community especially in developing countries. The purpose of this study is to analyze the relationship between sociodemographic characteristics, knowledge and practice of personal hygiene with the incidence of anemia among adolescent girls in Sirnagalih Village. The research method used was observational analytic using quantitative data with cross sectional design. Respondents of this study were 78 adolescent girls with purposive sampling technique and according to the inclusion and exclusion criteria. The data was collected by test of hemoglobin levels and filling out a questionnaire with the google form. The data analysis using univariate test to describe the variables of age, education, knowledge and practice of personal hygiene, also variables of anemia status in adolescent girls, bivariate test with fisher exact, and multivariate test using logistic regression. Based on the results of data analysis independent and dependent variables using the fisher exact test, the variables related to incidence of anemia were age obtained p= 0.023, knowledge of personal hygiene obtained p= 0.008, and practice of personal hygiene has p value= 0.045. The results of multivariate analysis that age was the most dominantly independent variables that influenced the incidence of anemia with a POR value of 17.860 (95% CI 1.819-175.349; p= 0.013). The conclusion of this study, there is a relationship between variables of age, knowledge and practice of personal hygiene with the incidence of anemia among adolescent girls in Sirnagalih Village.